STUDENTS’ PERCEPTION TOWARDS THE IMPLEMENTATION OF ENGLISH DISCOVERIES PLATFORM AT UIN SUNAN AMPEL SURABAYA - Islamiyah, Millatul; Dewi, Titis Kusuma; Jannah, Raudlotul (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
The advanced of technology demands changes in all aspect of life including education. Accordingly, the use of technology likely increases the effectiveness of teaching and learning. This research analyzes the use of English Discoveries (ED) platform as a media of technology embedded learning. Survey is used to collect what students perceive of using this such technological media learning in three different aspects such as accessibility, utility and affective behavior. Involving 265 students from education and teacher training faculty, the result shows positive attitude towards the implementation of ED. Interestingly, most students are motivated and willing to continue even recommend it to others regardless of the difficulties they encountered. More researches are highly suggested focusing on the integration of ED in online learning mode and teachers’ assistance and performance in face-to-face teaching mode to perform a blended learning.